Video PBL Cases and Accompanying Scripts: Abuse of a Child, STDs, Diabetes, Alzheimer's Disease (Out of Print) - Andria Thomas (Association of American Medical Colleges, 2006)
Abstract Introduction This resource contains four video problem-based learning (PBL) cases and accompanying scripts. These cases address the following clinical issues: child abuse, sexually transmitted diseases, diabetes, and Alzheimer's disease. Additionally, there are multiple psychosocial issues addressed in each including drug abuse, confidentiality, patient-physician communication, and access to care. Methods The child abuse, sexually transmitted diseases, and diabetes cases have a video and corresponding script, as well as a facilitator guide. The Alzheimer's case has a video and corresponding script. Results These video cases have been implemented for 4 months and initial feedback has been positive. No formal evaluation of effectiveness has been conducted at this time. Discussion Given the fact that a majority of medical schools utilize PBLs in their preclinical curricula, these cases are easily implemented in an educational setting. Further, the use of video components in this resource provides additional case-conceptualization by students.